2022
DOI: 10.1111/ijlh.13959
|View full text |Cite
|
Sign up to set email alerts
|

A stepwise haematological screening and whole‐exome sequencing reveal multiple mutations from SUPT5H causing an elevation of Hb A2 from a cohort of 47336 individuals

Abstract: Introduction Though an increase in Hb A2 is one of the most key markers of β‐thal carriers, a few independent cases are reported to show elevated Hb A2 levels caused by mutations in other genes beyond β‐globin gene. Methods We reviewed the haematological indices of 47336 individuals to analyse the phenotype–genotype correlation and identified 1439 individuals (3.04%) positive in the elevation of Hb A2. Globin and KLF1 genes analysis was performed, and further whole‐exome sequencing was carried to dissect the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…Taken together, the SUPT5H loss-of-function patient mutations result in a β-thalassemia trait-like phenotype unlinked to HBB. While we were conducting these studies, independent pedigrees with similar phenotypes were reported, lending further support to our genetic findings (Charnay et al 2022;Achour et al 2020;Lou et al 2022). Notably, patients harboring these mutations are relatively healthy, exhibiting subtle but consistent phenotypes: essentially no anemia, but clear signs of β/α-globin chain imbalance.…”
Section: Supt5h Variants Associate With An Unlinked β-Thalassemia Phe...supporting
confidence: 79%
“…Taken together, the SUPT5H loss-of-function patient mutations result in a β-thalassemia trait-like phenotype unlinked to HBB. While we were conducting these studies, independent pedigrees with similar phenotypes were reported, lending further support to our genetic findings (Charnay et al 2022;Achour et al 2020;Lou et al 2022). Notably, patients harboring these mutations are relatively healthy, exhibiting subtle but consistent phenotypes: essentially no anemia, but clear signs of β/α-globin chain imbalance.…”
Section: Supt5h Variants Associate With An Unlinked β-Thalassemia Phe...supporting
confidence: 79%